Nitrogen circulation in a Mediterranean holm oak forest, La Castanya, Montseny, northeastern Spain - Avila, Anna; Rodrigo, Anselm; Rodà, Ferran (Hydrology and Earth System …, 2002)
Bulk deposition, wet-only deposition, throughfall and dry deposition inferred from washing foliage and surrogate surfaces were used to describe inorganic N inputs to a forested catchment in the Montseny Mountains (La Castanya, Catalonia, Spain). Bulk inputs of inorganic N were moderate, with a mean of 5.7 kg N ha -1 yr -1 , ranging between 4 and 10 kg N ha -1 yr -1 for the period 1983 to 2000. Dry deposition fluxes estimated from washing branches added about 9 kg N ha -1 yr -1 to wet inputs and the total atmospheric deposition was estimated in 15 kg N ha -1 yr -1 . Despite this substantial input flux, nearly all the inorganic nitrogen was retained within the forest ecosystem: NH4 + and NO3 - concentrations decreased dramatically as water crossed the canopy and the soil profile. In the stream, at baseflow conditions, NH4 + and NO3 - concentrations were always below the analytical detection limit (< 2 µeq L -1 ). Only briefly during peak flows did NO3 - concentrations increase up to 100 µeq L -1 . Averaged over 10 years (1984-1994), the export of N at the catchment outlet was 0.05 kg N ha -1 yr -1 . This indicates a very tight N cycling allowing for an increase of N availability in these undisturbed forest ecosystems.
Keywords: ammonium; bulk deposition; Dry deposition; la castanya; montseny; nitrate; soil water; Spain; throughfall